2007
DOI: 10.1002/j.2050-0416.2007.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Representative Fungi from Shaoxing Rice Wine Wheat Qu Using a Polyphasic Approach of Culture-Based and Molecular-Based Methods

Abstract: J. Inst. Brew. 113(3), 272-279, 2007Ribosomal intergenic spacer analysis (RISA) and traditional culture-based methods were employed to examine the fungal community of Shaoxing rice wine wheat Qu. Results showed that RISA profiles of total DNA exhibited nine distinguishable bands. By comparison, the RISA fingerprints recovered from enrichment media gave variable patterns containing fewer bands. Bands corresponding to five fungal species detected by RISA of total DNA were also observed in RISA fingerprints from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 23 publications
2
79
0
Order By: Relevance
“…Because some of the materials used in Chinese rice wine brewing are not sterile, higher pitching rates are traditionally used to ensure that the inoculated yeast strain is the dominant strain and finishes the fermentation. wheat Qu is a source of many enzymes such as amylase, glucoamylase and protease 13,27 . Raw materials are degraded by these enzymes, producing nutritional components for yeast growth and fermentation.…”
Section: Small-scale Chinese Rice Wine Brewingmentioning
confidence: 99%
“…Because some of the materials used in Chinese rice wine brewing are not sterile, higher pitching rates are traditionally used to ensure that the inoculated yeast strain is the dominant strain and finishes the fermentation. wheat Qu is a source of many enzymes such as amylase, glucoamylase and protease 13,27 . Raw materials are degraded by these enzymes, producing nutritional components for yeast growth and fermentation.…”
Section: Small-scale Chinese Rice Wine Brewingmentioning
confidence: 99%
“…Research has generally focused on the enzymes and microorganisms of wheat Qu 24,30 , and the flavor of wheat Qu is judged by its simple sensory description with the term "normal or no odor of wheat Qu". It is the volatile compounds of wheat Qu however, that are the most important factors which influence the flavor of Chinese rice wine 23 , and for this reason it was important to analyze and characterize the volatile compounds from wheat Qu.…”
Section: Aspergillus Oryzae Emericella Nidulans Clavispora Lusitanimentioning
confidence: 99%
“…Wheat Qu is then incubated under spontaneous conditions for at least 15 days and stored for several months before being used to make Chinese rice wine. As a result of fermentation, wheat Qu is rich in various microorganisms such as Absidia corymbifera, Rhizopus oryzae, Rhizomucor pusillus, 30 . A wide variety of enzymes including amylases, glucoamylase, proteases, phytase and phosphatase also accumulate in the wheat Qu during fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the representative microorganisms in wheat Qu are Absidia corymbifera, Rhizomucor pusillus, Aspergillus fumigatus, Aspergillus orgyze, Rhizopus oryzae and a small amount of Penicillium sp., yeasts and bacteria (6)(7)(8). Wheat Qu provides the main microorganisms and the complex enzyme systems during a Chinese rice wine fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little research on the formation mechanism of the flavour compounds and the microorganisms in wheat Qu that directly affect the rice wine flavour. In general, the main flavour compounds in various rice wines (8,14,15) and Japanese sake (4,(16)(17)(18) are generated by the metabolism of the fungi. The objective of this study was to compare the volatile flavour compounds of the rice wines fermented with different kinds of wheat Qu samples, and to analyse the main species differences in the fungi.…”
Section: Introductionmentioning
confidence: 99%